Analisis Break Even Point (BEP) sebagai Alat Perencanaan Laba : Studi Kasus pada Pabrik Tahu Ud Pink Jaya - Adoe, Dea Ivana Angela (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the application of the Break Even Point (BEP) method as a tool in profit planning at the UD Pink Jaya Tofu Factory in Kupang City. This study uses a quantitative approach with a descriptive analysis method. Data collection techniques are carried out through interviews, documentation, and direct observation of the company's operational activities. The data studied includes fixed cost components, variable costs, sales volume, and selling prices from 2021 to 2024. The results of the analysis show that although the UD Pink Jaya Tofu Factory consistently records profits every year, the amount fluctuates. This condition indicates that profit planning has not been implemented optimally and systematically. By applying BEP analysis, companies are able to identify breakeven points or minimum sales limits that need to be achieved so as not to incur losses. In addition, this analysis can also be used as a basis for consideration in determining production strategies and determining selling prices in a more rational manner. The sustainable implementation of BEP is expected to help companies in improving cost efficiency, maximizing profits, and strengthening business competitiveness amid changing market dynamics.